Bilateral diffuse multiple cavitary nodules: a radiological presentation of adenocarcinoma - Spalgais, Sonam; Mathew, Libin; Mrigpuri, Parul; Kulshrestha, Ritu; Kumar, Raj (The Egyptian journal of chest diseases and tuberculosis, 2025)
The common causes of multiple cavitary lesions of lung are fungal pneumonia, pulmonary abscess, rheumatoid nodules, viral pneumonia, tuberculosis, and septic emboli. The cavitary lesions are seen in nearly 20% of lung cancers with most commonly squamous cell carcinoma. We present an adenocarcinoma of lung with bilateral cavitory lesion presenting as cough, breathlessness, and chest pain for 2 months. The cavitary lung lesions have multiple differential diagnosis and are difficult to differentiate on computed tomography findings. All cavitary lung diseases should be investigated with invasive procedure like bronchoscopy to confirm the diagnosis before empirical treatment.